Hukum korupsi di Indonesia perspektif multidisipliner - Tanjung, Irwansyah; Riyanto, Waryani Fajar (Fakultas Hukum Universitas Al Azhar Medan, 2024)
Corruption is not just a symptom, it has become a culture. In essence, corruption is a form of structural violence and cultural violence. Various approaches have been offered to provide solutions to eradicating corruption, but the results have not been optimal. In this paper, we will examine various approaches in various scientific disciplines (multidisciplinary: anthropology, morals, philosophy, law and education) to the problem of corruption, including multiple interpretations of terms, to be able to provide a comprehensive understanding. From an anthropological perspective, for example, corruption originates from the traditional concept of tribute, and this tribute tradition originates from the concept of offerings. Then in Islam there are also those who transcend the concept of tribute into zakat, and the concept of offerings with udhiyyah. In another perspective, these efforts include; moral force movement, dualism demarcation tactics and deliberative democracy (communicative action), criminal action (theft), and anti-corruption curriculum.